Kajian Hukum Praktik Kedokteran Pemeriksaan Selaput Dara Dengan Metode Tes Dua Jari - Sasongko, Purwanto Panji; Arimbi, Diah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Patients have the right to accept and refuse treatment, and the right to receive information from their doctor before giving Consent to Medical Action. Patients have the right to self-determination as a basis for human rights, and the right to information owned by the patient about their illness and what medical action is to be performed on them. To find out the hymen examination carried out by medical personnel or health workers who meet the principles of propriety and do not violate professional ethics. The research method used in this study is in accordance with normative juridical supported by prescriptives related to the protection of women's human rights against medical actions regarding hymen examination using the 'two-finger' test method. The results of the study on secondary data (primary, secondary and tertiary legal materials), then obtained on the technical implementation of the examination contained in the Standard Operating Procedure Guidelines for the Implementation of Minimum Service Standards (SPM) in the Field of Integrated Services for Women and Children Victims of Violence. The conclusion is that hymen examination using the 'two finger' test method is very contrary to the law, both in terms of the Medical Practice Law, contrary to the medical code of ethics, contrary to the regulations of the Minister of Health, contrary to Human Rights and contrary to the recommendations of the World Health Organization (WHO).